Staking out the unclear ethical terrain of online social experiments - Cornelius Puschmann; Engin Bozdag (Internet Policy Review, 2014)
In this article, we discuss the ethical issues raised by large-scale online social experiments using the controversy surrounding the so-called Facebook emotional contagion study as our prime example (Kramer, Guillory, & Hancock, 2014). We describe how different parties approach the issues raised by the study and which aspects they highlight, discerning how data science advocates and data science critics use different sets of analogies to strategically support their claims. Through a qualitative and non-representative discourse analysis we find that proponents weigh the arguments for and against online social experiments with each other, while critics question the legitimacy of the implicit assignment of different roles to scientists and subjects in such studies. We conclude that rather than the effects of the research itself, the asymmetrical nature of the relationship between these actors and the present status of data science as a (to the wider public) black box is at the heart of the controversy that followed the Facebook study, and that this perceived asymmetry is likely to lead to future conflicts.
Keywords: 300; Research ethics; Online social experiments; Data science; Transparency; Algorithmic curation